P-OT015. Monitoring prefrontal cortical activation while driving a vehicle: A functional near-infrared spectroscopy study. Issue 8 (August 2021) - Hirano, Daisuke; Kimura, Naotoshi; Nozawa, Hana; Enoki, Miku; Goto, Yoshinobu; Taniguchi, Takamichi
Abstract : Introduction . Functional near-infrared spectroscopy (fNIRS) is a non-invasive method to measure changes in oxygenated- and deoxygenated-hemoglobin concentrations in response to neural activation during specific tasks and stimuli. In this study, we monitored the brain activity of the prefrontal cortex in subjects while driving to investigate the effects of speed on brain activity. Methods . Twenty healthy subjects with driving experience drove their own vehicles about 100 meters at any speed (5 trials) and at highest acceleration speed (5 trials) and were told to stop at the stop line. Sixteen channels of fNIRS recording were placed to overlie the prefrontal cortex of the subjects during driving. The distance between the stop line and the vehicle when the vehicle comes to a stop and oxygenated hemoglobin concentration was compared between driving at any speed and driving at the highest acceleration. Results . Variation in the distance between the stop line and the vehicle was significantly greater when driving at the highest acceleration compared to driving at any speed. Oxygenated hemoglobin concentration recorded in the prefrontal cortex was significantly greater while driving a car to a stop at the highest acceleration than at free speed. Conclusion . Our findings suggest that driving at highest acceleration speeds requires more attention resources than driving at any speed. We have shown that monitoring brain activity using fNIRS has advantages and usefulness of in real driving.